Characteristics of sound interaction with materials - Seow, Yong Jie (2017)
High volume sound is known to be damaging to the human ear but even frequencies that are insensitive to human ear possess potential hearing issues. This thesis aim to investigate the best possible material for passive sound attenuation at various octave center frequencies. By performing an experiment with three materials (steel sheet, 2 –ply cardboard and acoustic foam) varied against four different frequencies (250, 500, 2000, 4000 Hz), their sound attenuation performance was noted and eventually analyzed against a composite material (dual material composite) configuration of materials. The steel sheet and foam configuration proved to be most effective, followed by the cardboard and steel sheet configuration. Results shows that composite materials do not sum up their sound attenuation effectiveness but instead follows a rule that relates to mass and stiffness of a material. Interestingly, other factors such as material structure and air gap affects the effectiveness significantly. Different materials have been discovered to work well against low frequencies or high frequencies but a composite material is not the only answer to a well-rounded sound frequency attenuation barrier.